Biological activity of secondary metabolites of actinomycetes and their potential sources as antineoplastic drugs: a review - Rui, Sun; Fengrui, Guo; Yining, Zhang; Hong, Shao; Xuewen, Yang; Changping, Wang; Chunjia, Yang (Frontiers in Microbiology, 2025)
Actinomycetes are an important group of Gram-positive bacteria, renowned for their ability to produce a wide array of structurally diverse and biologically active secondary metabolites. These secondary metabolites have significant applications in fields such as antimicrobial and antifungal treatments and show tremendous potential in cancer research. To comprehensively review the antitumor potential of actinomycetes-derived secondary metabolites, we conducted a systematic literature search across PubMed, Web of Science, and Scopus databases, covering the period from January 2019 to January 2024. The search used keywords including “actinomycetes,” “secondary metabolites,” “antitumor,” “cancer therapy,” “bioactivity,” and “clinical application.” A total of 95 relevant articles were identified through database searches. After applying inclusion and exclusion criteria, 87 articles were deemed eligible and fully reviewed in this article. These studies highlighted diverse structural classes of actinomycetes-derived antitumor compounds, including polyketides, non-ribosomal peptides, alkaloids, and terpenoids. Many of these metabolites exhibit potent anticancer properties through mechanisms such as inducing apoptosis, inhibiting proliferation, disrupting tumor microenvironment, and targeting key oncogenic signaling pathways. This review underscores the crucial role of actinomycetes secondary metabolites as an invaluable resource for antitumor drug discovery, offering new scientific insights into natural product-based cancer therapies, expanding the molecular toolbox for clinical oncology, and ultimately contributing to public health by advancing effective and innovative treatment options for cancer patients.